„ale jak se vožení, hned mu tíže“. Naplňování pohlavních rolí v básnické skladbě Stesk na ženitbu Hynka z Poděbrad - Martin Čapský (Theatrum Historiae)
The present study analyzes the poem “Complaint about the Marriage” by Hynek of Poděbrady from the last third of the 15th century. The youngest son of Bohemian King George of Poděbrady introduced the composition, which strengthened the distinction to the less noble men by the means of culturally constructed differences, to the aristocratic audience. Using the attributes of carnival entertainment, the author drew on the experience of his peers − starting a family and assuming the role of a farmer, including the difficulties associated with this transitional phase.